Antecedents of Environmentally and Socially Responsible Sustainable Consumer Behavior - Hosta, Maja; Zabkar, Vesna (Journal of business ethics, 2021)
Responsible sustainable consumer behavior (RSCB) involves a complex pattern of environmental and social issues, in line with the view of sustainability as a construct with both environmental and social pillar. So far, environmental dimension was far more researched than social dimension. In this article, we investigate the antecedents of both environmentally and socially RSCB and willingness to behave in environmentally/socially responsible way. We include measures of concern, perceived consumer control/effectiveness, personal/social norms and ethical ideologies/obligation to better explain and extend the traditional theory of planned behavior. Additionally, we test the impact of information availability about environmental or social impact on RSCB. Our findings on a representative sample of 426 respondents (ages 18 to 65) show that in general, antecedents of environmentally and socially responsible sustainable consumption are similar in their effect on consumer behavior, with personal norms, concern and ethical ideologies having the strongest impact on RSCB. When comparing both types of behavior, socially responsible behavior is more influenced by perceived behavioral control and possibly social norms than environmentally responsible behavior, while information availability plays its role for both behaviors. Sustainable responsible consumption can be achieved by embracing both dimensions of sustainability and consumers need to have a sense for both social and environmental issues. The complexity and struggles between doing what is good for environment and society could be the reason why consumers have difficulties achieving sustainable responsible consumption.